2016
DOI: 10.1038/hdy.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Sex change and effective population size: implications for population genetic studies in marine fish

Abstract: Large variance in reproductive success is the primary factor that reduces effective population size (N e ) in natural populations. In sequentially hermaphroditic (sex-changing) fish, the sex ratio is typically skewed and biased towards the 'first' sex, while reproductive success increases considerably after sex change. Therefore, sex-changing fish populations are theoretically expected to have lower N e than gonochorists (separate sexes), assuming all other parameters are essentially equal. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…The majority of contemporary LDNE-based N e values we derived are smaller than those reported (using different microsatellite markers) for E. marginatus-an endangered grouper species with similar life history characteristics to Nassau grouper (Schunter et al, 2011). However, the smallest contemporary N e value observed (Abaco: 375) was similar to those reported for other teleosts (e.g., Santer and Slinger sea bream, Cheimerius nufar and Chrysoblephus puniceus; Coscia et al, 2016).…”
Section: Effective Population Size and Population Bottlenecksmentioning
confidence: 41%
See 1 more Smart Citation
“…The majority of contemporary LDNE-based N e values we derived are smaller than those reported (using different microsatellite markers) for E. marginatus-an endangered grouper species with similar life history characteristics to Nassau grouper (Schunter et al, 2011). However, the smallest contemporary N e value observed (Abaco: 375) was similar to those reported for other teleosts (e.g., Santer and Slinger sea bream, Cheimerius nufar and Chrysoblephus puniceus; Coscia et al, 2016).…”
Section: Effective Population Size and Population Bottlenecksmentioning
confidence: 41%
“…Variability in N e estimates has been linked to differences in reproductive success and/or the methods used in their computation (Hare et al, 2011;Waples et al, 2013Waples et al, , 2014Coscia et al, 2016;Waples and Anderson, 2017). For example, Waples et al (2014) demonstrated that N e estimates based on a variety of age-structured samples are likely to be underestimated due to Wahlund effects.…”
Section: Effective Population Size and Population Bottlenecksmentioning
confidence: 99%
“…Hauser et al (2002) estimated N e in C. auratus populations from New Zealand and found that N e was five orders of magnitude below the adult census size (N). Several suggestions have been made regarding the factors that may contribute to very low estimates of N e , such as high fecundity and biased reproductive success (Hauser et al 2002;Hauser and Carvalho 2008;Coscia et al 2016;Waples 2016). Using simulated data, Waples (2016) explored, in turn, the potential effects of increased longevity, fecundity and variance in reproductive success, as well as increased egg quality with age, and found that 'very tiny' N e required some version of Hedgecock's (1994) 'sweepstakes' hypothesis, whereby only a few families reproduce successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA is maternally inherited. For this reason, the inheritance patterns of protogynous hermaphrodites differ to that of species that do not practice sex reversal (Coscia et al, 2016). Therefore, it may be important to include both nuclear and mitochondrial markers to explore the population genetics of sex reversal fish.…”
Section: Introductionmentioning
confidence: 99%